Inovasi Manajemen Pendidikan di Lembaga Pendidikan Islam - Yanti Nurdiyanti; Irpan Ilmi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This scientific article aims to examine Educational Management Innovation in Islamic Educational Institutions. The type of research used in this study is library research, namely the problems and data collection of this study are sourced from primary data (main) and secondary data (supporting data). The data collection technique in this study is documentation, and the analysis method uses content analysis. The results of the analysis show that the concept of developing Islamic educational management is formulated with the following steps: First, formulating a shared understanding of the meaning and significance of education. Second, formulating an education system based on Islamic values. Third, the concept of developing Islamic educational management is based on the spirit of strengthening the curriculum. Fourth, formulating precise objectives while determining educational tasks. Fifth, becoming an alternative in responding to the challenges of an increasingly complex era. One form of innovation in Islamic educational institutions is the spirituality atmosphere-organized work-based management model accompanied by good educational programs, complete facilities and infrastructure and the availability of funds. Management innovation in Islamic educational institutions is carried out to answer challenges and provide responses to advances in science and technology, behavioral changes, social adjustment. The development of Islamic educational management with; 1) strengthening Islamic values, 2) structural and cultural transformation and 3) improving the quality of education.